Przerzuty nowotworowe do naczyniówki gałki ocznej. Przegląd metod leczenia ze szczególnym uwzględnieniem radioterapii - Sas-Korczyńska, Beata; Romanowska-Dixon, Bożena; Skołyszewski, Jan; Lesiak, Jan (Klinika Oczna / Acta Ophthalmologica Polonica, 2006)
Choroidal metastases are developed in 4 – 12% of patients with solid malignancies. Typical symptoms are loss of visual acuity or visual field, photophobia and floaters. In therapy of choroidal metastases are used following methods: surgery, laser photocoagulation, radiotherapy, and systemic treatment (anti-neoplastic chemotherapy or hormonotherapy). At choice of method of treatment it is taking not only features associate with choroidal metastases (as size, shape, number of changes and localization) but also: performance status of patient and the presence of metastases in any sites. The purpose of this paper is the review of treatment methods of choroidal metastases with special regard to application of radiotherapy. Radiotherapy is a conservative method of treatment, and it is used as brachytherapy or external beam irradiation (teleradiotherapy). Brachytherapy is recommended in case of single change, with base diameter below 18 mm. The positive results are observed in 90% cases. Teleradiotherapy is used in metastatic tumours which size exceed possibility successfully using of brachytherapy, and in case of multiple foci of choroidal changes, and metastases bilaterally localized. 70 – 89% patients developed regression of choroidal metastases after external beam irradiation. The preservation of bulbus oculi is observed in 98% patients. Presented paper showed application of methods of brachytherapy used in Ophthalmological Department of Jagiellonian University, and technique of teleradiotherapy used in Radiotherapy Department of Oncology Centre in Krakow, which are used in treatment of choroidal metastases.